Looking back at the 2011 EcoZD meeting in Bangkok - Asse, Rainer (International Livestock Research Institute, 2011)
Between 10-13 December 2011, ILRI convened the Progress meeting on Ecosystem approaches to the better management of zoonotic emerging infectious diseases in the South East Asian Region. Here, Rainer Asse from ILRI details the main talking points from the meeting.